(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
As time goes on, more and more individuals rely on social networks. People in the student demographic make up the bulk of social media users due to the amount of time they spend on these platforms. Examining how high school students’ use of social media, particularly Facebook, affects their academic achievement is the primary goal of this research. The research relied on students’ social media use and grade point averages from four separate classes. We may deduce this link and what it means by using statistical analysis. For everyone right now, social media is essential for communicating with others, sharing and asking information, and following, evaluating, and interpreting current events, among other things. This study aimed to assess the pros and cons of students’ use of social networking sites in relation to their study habits and performance. Two hundred and twenty students from a higher education vocational school participated in the research. A questionnaire was developed to obtain students’ perspectives regarding digital technology and social media, and here is how the data was acquired. According to the findings, students’ study habits and digital technology use are negatively affected. The research offered several recommendations based on the results.